Human Health Monitoring by Sensors: Analysis of Contextual Uncertainties through Dempster-Shafer Evidence Theory - Silva, Katia Cilene Neles; Bressan, Graça (INFOCOMP Journal of Computer Science, 2017)
This paper describes the authors’ observations about the uncertainties associated with monitoring based on sensors, through the Dempster-Shafer Evidence Theory. It presents the results of an experiment which is part of an ongoing research about dealing with uncertain contextual information in the human health monitoring system based on sensors. The experiment employs evidence theory on reasoning over context. Recommendations to improve the systems to monitor the human health within a framework that addresses uncertainty are also provided.